Breaking the Metal Ceiling : Female Entrepreneurs Who Succeed in Male-Dominated Sectors in Uganda - Campos, Francisco; Goldstein, Markus; McGorman, Laura; Munoz Boudet, Ana Maria; Pimhidzai, Obert (World Bank, Washington, DC, 2016)
Worldwide, female entrepreneurs tend to experience lower productivity and profit than their male peers. One reason for this is that women tend to be concentrated in less profitable businesses. This mixed methods study from Uganda investigates a range of factors that may hinder or help female entrepreneurs move into male-dominated sectors, where they are as successful as men, and significantly more successful than women who remain in traditionally female sectors. This analysis finds that information gaps about the relative profitability of male-dominated businesses play an important role, as do the types of role models influencing youth as they determine their career paths. Informational campaigns, as well as apprenticeship and mentorship programs, present potential policy options.